2011
DOI: 10.1007/s00464-011-1672-7
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive film for anchoring assistive surgical instruments in endoscopic surgery: in vivo assessment of deployment and attachment

Abstract: Mucoadhesive anchoring represents a completely biocompatible and safe solution for stable positioning of AISI onto mucosal tissue. This novel polymeric mechanism can be useful for designing intraluminal accessories and tools that enhance surgeons' performances in endoluminal procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Numerous studies have exploited mucoadhesion further by developing mucoadhesives to chemically bond to the mucosa to improve traction and/or adhesion. This can result in significantly higher adhesive forces while, in some cases, maintaining the ability to repeatedly reattach to the mucosa [151][152][153][154].…”
Section: Adhesionmentioning
confidence: 99%
“…Numerous studies have exploited mucoadhesion further by developing mucoadhesives to chemically bond to the mucosa to improve traction and/or adhesion. This can result in significantly higher adhesive forces while, in some cases, maintaining the ability to repeatedly reattach to the mucosa [151][152][153][154].…”
Section: Adhesionmentioning
confidence: 99%
“…Dodou et al have shown that high static friction could be created between a colonoscopic device and the GI wall due to mucoadhesion (Dodou et al 2006;Dodou et al 2005). In the work of Paolo Dario et al (Pensabene et al 2011;Quaglia et al 2013), mucoadhesive patches have been tested and assembled with a release mechanism in the CEs. Additionally, it has been shown that with 5 N preload force, 110 min stable anchoring could be achieved for a 10 mm diameter mucoadhesive patch.…”
Section: Introductionmentioning
confidence: 97%
“…Localized drug delivery was achieved by magnetic retention under biplane fluoroscopy in a study by Laulicht et al (122), in which a drug-loaded magnetic capsule was held in a specific position of the GI tract. A future prospect for drug delivery over time is the use of mucoadhesives to stably attach the capsule to a desired point in the GI tract without the need for magnetic fields, as suggested by Pensabene et al (128). This adhesive technology is reversible, and detachment occurs after a certain time that can be trimmed by adjusting the polymer formulation.…”
Section: Therapy Deliverymentioning
confidence: 99%